2022
DOI: 10.1515/tjb-2020-0619
|View full text |Cite
|
Sign up to set email alerts
|

The effect of virtual laboratory simulations on medical laboratory techniques students’ knowledge and vocational laboratory education

Abstract: Objectives Virtual laboratory simulations (VLSs) are computer-based tools that offer unlimited application options in scientific, medical, and engineering fields. The aim of this study was to evaluate whether VLSs are efficient learning tools and how these simulations can be integrated into laboratory practice in medical laboratory education. Methods In this pre-test/post-test control group study, 32 volunteers were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…These results show that the material contained in the virtual laboratory is quite clear and easy for students to understand, whereas several studies have shown that the clarity of a learning resource product will make it easier for students to understand the material they are studying (Hsiung, 2018). The use of virtual laboratories will provide many benefits to students and access to a variety of resources, including data sets, experimental videos, and interactive assignments, which, of course, will contribute to the student's overall learning experience (Keleş et al, 2022;Muslim et al, 2022). Therefore, material aspects such as the actuality and accuracy of the material in a virtual laboratory are very important to look at, considering that the impact on student learning outcomes will also be considerable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show that the material contained in the virtual laboratory is quite clear and easy for students to understand, whereas several studies have shown that the clarity of a learning resource product will make it easier for students to understand the material they are studying (Hsiung, 2018). The use of virtual laboratories will provide many benefits to students and access to a variety of resources, including data sets, experimental videos, and interactive assignments, which, of course, will contribute to the student's overall learning experience (Keleş et al, 2022;Muslim et al, 2022). Therefore, material aspects such as the actuality and accuracy of the material in a virtual laboratory are very important to look at, considering that the impact on student learning outcomes will also be considerable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the integration of virtual labs in biology learning allows students to carry out practical experiments and simulations virtually, which can improve their understanding of the material being taught (Kadek Suartama et al, 2020). Not only are there benefits from an academic perspective, but implementing the inquiry model with a virtual lab can also improve students' scientific literacy, learning motivation, and questioning skills (Keleş et al, 2022). With an innovative learning model such as this, students will be actively involved in deepening their understanding of complex biological concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the teaching and learning of science are closely connected to laboratory exercises [1][2][3][4][5]. Laboratories provide controlled environments that ensure the safety of students as they put theory into practice [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Digital tool barriers can negatively impact distance education, including online learning, virtual learning environments, and digital/online lab courses (Bawa, 2020). At the instructional level, barriers include cost, accessibility among students, lack of instructor training, and instructor and student resistance to change (Chidzonga et al, 2022;Guzman-Cole et al, 2022;Keleş et al, 2022). At the institutional level, challenges exposed during emergency remote teaching (ERT) included inadequate infrastructure, lack of technical expertise for digital tool implementation, incompatibility with existing equipment and software, poor maintenance and support, and insufficient data security of personal information (Butt et al, 2022;Chidzonga et al, 2022).…”
Section: Digital Tool Retention: Post Pandemicmentioning
confidence: 99%
“…The research literature provided insight into the pandemic-induced and current digital tool use and biology and microbiology lab course trends. Instructional-level barriers, such as cost, accessibility among students, lack of instructor training, as well as instructor and student resistance to change, course-level requirements, and lab skill development, positively effects the adoption of digital tools (Chidzonga et al, 2022;Guzman-Cole et al, 2022;Keleş et al, 2022).…”
Section: Digital Tool Trendsmentioning
confidence: 99%